Applying Citizens' Juries to the Global South - Nilgen, Marco; Vollan, Björn (CGIAR, 2023)
Employing Citizens’ Juries (CJs) for Identifying Pathways to More Sustainable Food Systems is one of the proposed research endeavors of work package 3 (WP3) within the One-CGIAR initiative “Mitigate+: Low-Emission Food Systems” (2022-2024). Applying a Living Labs (LLs) approach, WP3 (also called, Living Labs for People or LL4P) implements participatory action research to support food system (FS) stakeholders and partners in important FSs to co-design, experiment, and implement integrated socio-technical innovation packages to reduce GHG sources and enhance sinks, whilst improving social outcomes and providing public good co-benefits. In this context, we aim to organize and analyze CJs in one LL4P site (Colombia) in 2023 and 2024 to complement other activities in achieving the LL4P outcomes. In CJs, bottom-up decision-making processes are facilitated by the incorporation of balanced expert knowledge and stakeholder input supplemented by alternative forms of learning. CJs create spaces where randomly selected representatives of the respective target population deliberate on an issue of public importance, before making policy recommendations based on these deliberations. In this way, local knowledge and stakeholder interests are blended with expert information to inform policy decision-making (Coote & Lenaghan, 1997; Crosby, 1995; The Jefferson Center, 2004; Wakeford et al., 2015).